Análisis del desempleo y subempleo en el Ecuador en el período 2007-2017 - Toledo Toledo, María Fernanda (2019)
The present research focuses on the analysis of the evolution of unemployment and underemployment in Ecuador for the period 2007-2017, Therefore present statistical data on the basis of the unemployment rate of Ecuador with regard to Latin America; it was also analyzed the total unemployment rate of the urban and rural sector of Ecuador as well as their most essential provinces; In addition, the unemployment rate by gender and age in our country is identified for the period of analysis. The study also refers the underemployment by identifying its total rate, underemployment in both the urban and rural sectors and the most important provinces of our country, underemployment by the branch of economic activity, gender and age was also analyzed. The research is descriptive with a qualitative approach, the data were obtained from official sources of reports issued by the Central Bank of Ecuador, the National Institute of Statistics and Census and the International Labor Organization. In the analysis and discussion of results it was evident that there was higher unemployment in 2008 and 2009 due to the international economic crisis, the validity of the new Labor Code, which gave more rights to workers in their remuneration and work environment; accompanied by the fall in the price of the barrel of petroleum which led to that in the period indicated there was an economic stagnation, being the most affected cities Quito and Guayaquil.